The Effects of Service Quality, Healthcare Facilities, and Waiting Time-Patient Trust on Patient Satisfaction at Urip Sumoharjo Hospital, Bandar Lampung - Febi Faulina; Nadia Riska Oktari; Indah Permata Sari; Febrianty Febrianty; Reza Hardian Pratama (IJBLE Scientific Publications Community Inc., 2026)
Patient satisfaction is a critical outcome indicator for hospital performance because it reflects how patients evaluate the technical, functional, and environmental aspects of care. This study examined the effects of service quality, healthcare facilities, and waiting time-patient trust on patient satisfaction at Urip Sumoharjo Hospital, Bandar Lampung. A quantitative cross-sectional explanatory design was employed. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using partial least squares structural equation modeling (PLS-SEM). The study involved 90 respondents, with demographic data indicating that 64.44% were female and 61.11% were younger than 25 years. The measurement model screening retained indicators with adequate outer loadings and removed weaker items below the recommended threshold. The structural model showed strong explanatory power, with service quality, healthcare facilities, and waiting time-patient trust explaining 70.8% of the variance in patient satisfaction (R² = 0.708; adjusted R² = 0.697). Path analysis demonstrated that service quality had a positive and significant effect on patient satisfaction (β = 0.345; t = 4.215; p < 0.001), followed by waiting time-patient trust (β = 0.312; t = 3.890; p < 0.001) and healthcare facilities (β = 0.289; t = 3.182; p = 0.001). These findings indicate that patient satisfaction is shaped not only by tangible facilities but also by reliable, responsive, and trustworthy service processes. Hospital management should prioritize staff responsiveness, communication clarity, waiting time control, facility cleanliness, and equipment readiness to strengthen patient-centered service quality.